Effect of artemether on phosphorylase, lactate dehydrogenase, adenosine triphosphatase, and glucosephosphate dehydrogenase of Schistosoma japonicum harbored in mice. - Xiao Shu-hua; You Ji-qing; Guo Hui-fang; Mei Jing-yan; Jiao Pei-ying; Yao Min-yi; Zhuang Zhao-nong; Feng Zheng (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of artemether (Art) on phosphorylase (PP), lactate dehydrogenase (LDH), glucose-6-phosphate dehydrogenase (G-6-PDH), and adenosine triphosphatase (ATPase) of S japonicum. METHODS: Mice infected with S. japonicum cercariae for 32-38 d were treated i.g. with Art 100-300 mg.kg-1 and killed 24-72 h after treatment for collection of schistosomes. The activities of PP, LDH, and G-6-PDH were measured by the formation of NADH or NADPH. The activity of ATPase was measured by the rate of release of inorganic phosphate (Pi) from ATP at 37 degrees C. RESULTS: After infected mice were treated i.g. with Art 300 mg.kg-1 for 24-48 h, the activities of total PP and PPa (active form) increased markedly in both male and female worms, while PPb (inactive form) showed no or only a slight increase. At 24-72 h after the above-mentioned mice were treated i.g. with Art 100-300 mg.kg-1, the inhibitory rates of LDH and G-6-PDH were 9%-59% (male) and 41%-75% (female) as well as 22%-42% (male) and 74%-89% (female), respectively. When Art 300 mg.kg-1 was given to infected mice for 24 h, only the activity of Mg(2+)-ATPase showed marked inhibition in both male and female worms. At 48 h, the Ca(2+)-ATPase, Mg(2+)-ATPase, and Na(+)-K(+)-ATPase were all inhibited, the inhibitory rates of 17% (male) and 19% (female), 32% (male) and 48% (female) as well as 29% (male) and 44% (female), respectively. CONCLUSION: In schistosomes, the increase in the activity of AMP-independent PPa induced by Art may enhance the decomposition of glycogen and the inhibition of LDH by Art could reduce the formation of lactate. Moreover, Art exerts a potent inhibition on the G-6-PDH activity of the female S japonicum.